Revoluções da linguagem estética: a escola Bauhaus (1919-1933) - Dolzan, Jorge Elias (2008)
This work want to show that the history of design, understood here as language, was marked by revolutions. The origin of design occurs during the Industrial Revolution, meantime was in the epoch between the two heavy wars of the 20th century, that the Bahuaus School was define this area, allowing their understanding and action. Influenced by the Circle of Viena, Scholl of Frankfurt and Praga, this institution has define the design and aesthetics modern language. The objective of this work is to analyze the Bauhaus contributions for the “revolution” aesthetics of design and, consequently, of the modern aesthetic language. In addition to the acknowledgement of historical moment, this dissertation present the analysis of two chairs (one in Art Noveau and the other of the Bauhaus) and project of contemporary interior’s design, allowing understand that what has been developed in that school still remains symbol of modernity, aesthetic language inexistent before their time